IMPLEMENTASI ASAS-ASAS HUKUM EKONOMI SYARIAH DALAM PENGEMBANGAN MART 212 PADA 212 MART MUHAJIRIN PALEMBANG - Yogi, Yogi; fauziah, fauziah; armasito, armasito (Muamalah, 2020)
ABSTRACT 212 Mart Muhajirin Palembang is a Mart that was founded in the spirit of the Muslim community, which was initiated by the action of defending Islam against religious blasphemy. Which is the implementation of the Islamic defense action, namely by building a business in the retail trade sector. This is what motivates the author to raise the title "Implementation of Islamic Economic Law Principles in the Development of the 212 Mart in Palembang City (Case Study 212 of the Muhajirin Mart Palembang). As one of the retail businesses built by Muslims and with a passionate background to build the economy of Muslims, it is fitting that the 212 Mart Muhajirin Palembang apply Islamic principles in developing its business. Therefore this thesis is made to answer the problem (1) how is the implementation of the principles of Islamic economic law at 212 Muhajirin Mart Palembang (2) how is the suitability of the implementation of the principles of Islamic economic law at 212 Mart Muhajirin Palembang with the principles of Islamic economic law . The type of research that the writer uses in this research is field research. Samples were taken by purposive sampling with primary and secondary data sources. Furthermore, the analysis is carried out in a descriptive qualitative manner, which will explain all existing problems then draw conclusions and general statements are drawn to specific statements. 212 Mart Muhajirin Palembang has implemented the principles of Islamic Economic Law as a whole, starting from the principle of monotheism, the principle of justice, the principle of maslahat, the principle of helping and the principle of balance in the development of its Retail trading business, this can be seen from the implementation of sales- purchase, cooperation agreements and social activities that are carried out outside of operational activities. So the implementation of the principles of sharia economic law is in accordance with the Sharia Economic Law. Keywords: Implementation, principle of monotheism, principle of justice, principle of benefit, principle of mutual help, principle of balance, mart 212.